SILVER NITRATE AND BIO-SILVER NANOPARTICLES ON SOME MORPHOLOGICAL, PHYSIOLOGICAL, AND ANATOMICAL VARIATIONS OF TOMATO PLANTS (Nativa, 2025)
An experiment in a greenhouse was conducted to study the influence of silver nitrate and silver nanoparticles on morphological, physiological, and anatomical characteristics of tomato plants. Silver nanoparticles were synthesized using green tea extract as capping and reducing agents. As observed in FE-SEM images, the biosynthesized silver nanoparticles were circular with a diameter of 61 ± 6 nm. The following effects were observed: i) Morphology: Silver nitrate positively influenced the character of plant length, root length, root dry weight and root fresh weight. ii) Physiology: When tomato plants were treated with Bio-AgNPs and silver nitrate, antioxidant enzymes (SOD and Catalase) and chlorophyll were increased, while total sugar content in tomato leaves was decreased. Silver in silver nitrate or silver nanoparticles did not significantly affect proline content. iii) Anatomy: Exposure to Bio-AgNPs resulted in decreased cortex thickness, vascular bundle length, and the appearance of dark regions in the intercellular space in tomato stem pith and cortex tissues. In contrast, exposure to silver nitrate resulted in decreased stomatal length on both leaf surfaces, decreased number of stomata on the upper surface, and increased number of stomata on the lower leaf surface, compared to other treatments.Keywords: Bio-AgNPs; phytotoxicity; heavy metals; plant growth; chlorophyll; catalase; plant anatomy. Silver nitrate and bio-silver nanoparticles on some morphological, physiological, and anatomical variations of tomato plants RESUMO: Um experimento em uma estufa de produção vegetal foi conduzido para estudar a influência do nitrato de prata e de nanopartículas de prata em caracteristicas morfológicas, fisiológicas e anatomicas de plantas de tomate. Nanopartículas de prata foram sintetizadas usando extrato de chá verde como agentes de cobertura e redução. Por imagens de FE-SEM, as nanopartículas de prata biossintetizadas apresentavam formato circular com um diâmetro de 61 ± 6 nm. Foram observados os efeitos: i) morfologia: O nitrato de prata influenciou positivamente o caráter do comprimento da planta, comprimento da raiz, peso seco e fresco da raiz. ii) fisiologia: quando as plantas de tomate tratadas com Bio-AgNPs e nitrato de prata, as enzimas antioxidantes (SOD e catalase) e clorofila foram aumentadas, enquanto o conteúdo de açúcares totais nas folhas de tomate foi diminuído. A prata, seja em nitrato de prata ou nanopartículas de prata, não afetou significativamente o conteúdo de prolina. iii) Anatomia: a exposição a Bio-AgNPs resultou na diminuição da espessura do córtex, no comprimento do feixe vascular e no aparecimento de regiões escuras no espaço intercelular nos tecidos da medula e do córtex do caule do tomateiro. Em contraste, a exposição ao nitrato de prata resultou na diminuição do comprimento dos estômatos em ambas as superfícies foliares, na diminuição do número de estômatos na superfície superior e, ao mesmo tempo, no aumento do número de estômatos na superfície inferior da folha, em comparação com outros tratamentos.Palavras-chave: Bio-AgNPs; fitotoxicidade; metais pesados; crescimento de plantas; clorofila; catalase; anatomia vegetal.